PENGARUH MOTIVASI KERJA, LINGKUNGAN KERJA, DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DINAS PARIWISATA KABUPATEN TIMOR TENGAH SELATAN - Suprihatmi Sri Wardiningsih, Vebe Selan, Amin Wahyudi & (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2016)
Performance is the result of the quality and quantity of work accomplished by an employee in carrying out their duties in accordance with the responsibilities given to the employees. Some important factors to improve performance is work motivation, work environment and work Discipline. The purpose of this study to determine the effect of work motivation, work environment and work Discipline on Employee Performance Office of Timor Tengah Selatan regency tourism. The population in this study were all the staff of Department of Tourism of Timor Tengah Selatan regency totaling 32 people, the samples in this study were all employees of the department of tourism of Timor Tengah Selatan district used as the respondents (32 respondents). The sampling technique in this study using sampling methods saturated. The data in this study were obtained directly from the results of questionnaires. The analytical tool used is Test Instruments Research, Classical Assumption Test and the Linear Regression Test, Test F and Test R2. The results showed that work motivation significantly influence the performance of employees, working environment have a significant effect on the performance of employees, working Discipline significant effect on employee performance. The most dominant variable influence on employee performance is the motivation work because these variables have the greatest regression coefficient (0,990). The conclusion was that work motivation, work environment and work Discipline everything positive and significant effect on the performance of employees. Keywords: work motivation, work environment, work discipline, employee performance.